Exciter laser coronary atherectomy (ELCA) can be a powerful weapon in the treatment of chronic thromboembolic pulmonary hypertension (CTEPH). (March 2022) - Tang, Heng; Gan, Hongbo; Yang, Hong; Wen, Li; Pu, Peng
Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is mainly due to pulmonary vascular thrombosis causing pulmonary vasoconstriction and thrombosis, leading to pulmonary vascular remodeling, the formation of irreversible pulmonary arterial pressure rise, and ultimately producing serious right heart failure. It is the only curable subtype of pulmonary hypertension, mainly secondary to acute pulmonary embolism (PE), which is not rare but has a high disability rate and mortality rate. Early diagnosis and timely treatment can significantly improve the prognosis of CTEPH patients. However, the effective treatment of CTEPH has high requirements for patients, and most patients cannot be treated by surgery, resulting in high mortality. Excimer laser coronary atherectomy (ELCA) is a new percutaneous coronary intervention (PCI), which can decompose the blocking components in blood vessels through photochemical, photothermal, and photomechanical actions, and it can be used to remove thrombus, plaque, calcified lesions, and tissues. At present, it is mainly used in complex coronary artery disease, which not only improves the success rate but also reduces the incidence of complications. It showed significant advantages in the treatment of complex and refractory coronary artery disease. However, the clinical application of ELCA is limited to the coronary artery, and there is no report yet on the application of ELCA to other blood vessels in the human body, such as the pulmonary static artery. Based on the above situation, we made a basic review of ELCA and CTEPH and we discussed the hypothesis that ELCA, giving good results in complex coronary lesions, could also be applied to CTEPH.